PENGARUH MODEL PEMBELAJARAN INQUIRY BASED LEARNING BERBANTUAN MEDIA YOUTUBE TERHADAP KETERAMPILAN MENULIS TEKS ULASAN MAHASISWA - Hafizah; Maya Tya Ningrum, Desy (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Abstract The implementation of the research is based on the importance of review text writing skills for students as a means of critical and creative thinking. It is known that PGSD students at Bhayangkara University, Greater Jakarta still experience difficulties in identifying the identity of the text, understanding the information contained in the text, the opinion of the text author, comparing the text being reviewed with similar ones, and are unable to determine the strengths and weaknesses of the text critically and creatively. Therefore, we need an Inquiry Based Learning model assisted by YouTube media to have a positive influence on students' review text writing skills. This research aims to determine whether there is an influence of the Inquiry Based Learning model assisted by YouTube media on students' ability to write review texts. The research method used is an experiment with a Nonequivalent Control Group Design research design. Data were analyzed by carrying out normality tests, homogeneity tests, and hypothesis tests (t-test). The research results show that there is a significant influence in the application of the Inquiry Based Learning model assisted by YouTube media for students with a value of sig.0.001. Keywords: Inquiry Based Learning, review text, Youtube